Association between elevated serum uric acid levels and islet beta cell function indices in newly diagnosed type 2 diabetes mellitus-a one year cross sectional study at tertiary care center - Gupta, Kopal; P., Haritha; Kothiwale, V. A. (International Journal of Research in Medical Sciences, 2023)
Background: Serum uric acid (SUA) has been reported as a risk factor for type 2 diabetes mellitus (T2DM). Even though various studies concluded that SUA plays an essential role in DM onset, association between SUA and pancreatic islet β cell function and the effect of gender and body mass index (BMI) on it in is still unclear. Methods: A hospital based one-year cross-sectional study was conducted and required data was collected from 76 patient who were newly diagnosed T2DM. All patients were investigated for SUA, and homeostasis model assessment-insulin resistance (HOMA-IR) was calculated using the HOMA2 calculator. Results: Mean SUA level among the males was 4.65±1.81 mg/dl and among the females was 4.31±1.94 mg/dl. β pancreatic cell function index was estimated using HOMA-IR. Mean HOMA-IR level among the male study population was 5.01±7.44 and 5.02±4.63 among the females. A positive and significant correlation was observed between SUA and HOMA-IR (r=0.2283, p=0.0489) at 5% level, and was more pronounced among the female population (r=0.5127, p=0.0175). Correlation between HOMA-IR and BMI was found to be positive and significant (r=0.4948, p=0.0001). On plotting multiple regression analysis, coefficient of determination (R²) was 0.8374 (p<0.05), indicating significant contribution of all variables when combined towards HOMA-IR. Conclusions: Present study demonstrates that SUA harbours a positive and significant correlation with pancreatic islet β cell function index among newly diagnosed T2DM patients and is influenced by gender and BMI.